Coverage control strategy for directional sensor networks - LI Jing; WANG Ru-chuan; HUANG Hai-ping; SUN Li-juan; XIAO Fu; JIANG Ling-yun (Tongxin xuebao)
Aimed at disadvantages on most existing coverage control algorithms for directional sensor networks,such as finite orientations,the restrained degree of optimization,the deficient applicability of these algorithms etc.,a coverage control strategy（CCS） was presented,which was strictly deduced from some mathematic properties.A distributed algo-rithm generated from the CCS could be extensively used in different kinds of networks with different sensing models.Simulation results and performance analysis illustrate that the CCS can efficiently enhance the coverage of networks and show the certain superiority comparing to existing algorithms of the same kind.